Communication of emotional nature in virtual space: quantitative questions on a chat corpus - Lazar, Jan (Romanica Olomucensia, 2015)
The enormous development of new communicative technologies, among which electronic communication plays a prominent role, is one of the main characteristics of life today. Nowadays, computer-mediated communication has become so common and easy that it is no longer possible for us to ignore it. Although the communication in chat rooms is never produced face-to-face, it could preserve some of the characteristics of real communication. This type of communication, in the absence of sense contact and para-verbal features, adds another scale of features to the "spoken" theme that are largely able to replicate spontaneous oral communication. It is advisable to make it clear that these features may be subdivided in two groups: first, the intentional artifacts formed by server creators (e.g., smileys); second, the creative processes invented by users (e.g., personalization of the written). In this article, the questions of how and to what extent these features allow emotional expression in chats are posed.
Keywords: computer-mediated communication; Internet; chat; emotion